Exploring pathways between internalized weight bias, eating disorder psychopathology, and weight loss expectations in treatment-seeking adults with binge eating and obesity - Katrina T. Obleada; Adrian Ortega; Isabel R. Rooper; Leah M. Parsons; Macarena Kruger; Chidiebere Azubuike; Lindsay D. Lipman; Diane Chen; Jennifer E. Wildes; Andrea K. Graham (Eating and Weight Disorders)
Abstract Purpose Individuals with obesity and binge eating face weight stigma, which can lead to internalized weight bias (IWB), reinforce eating disorder (ED) pathology, and promote unrealistic weight loss expectations (WLE). Greater understanding of pathways between IWB, ED pathology, and WLE could inform interventions to promote healthy WLE and reduce IWB. This study explored pathways through which IWB directly and indirectly relates to eating pathology and WLE in treatment-seeking adults with obesity and recurrent binge eating. Methods Participants (N = 199, Mage = 40.3, SD = 14.3) completed the Eating Disorder Examination interview (EDE) and questionnaire (EDE-Q), Modified Weight Bias Internalization Scale, and Positive and Negative Affect Scale. WLE were calculated based on participants’ expected weight loss divided by current weight. We hypothesized that greater IWB would be associated with greater eating pathology and higher WLE. Pearson correlations were examined to identify possible pathways, followed by exploring direct and indirect associations for pathways with significant correlations. Results IWB was positively correlated with Eating and Shape Concerns, as well as negative affect (p < 0.05), but not with WLE. Negative affect was positively correlated with WLE. In the pathway model, IWB was directly, negatively associated with WLE (b = − 0.02, p < 0.05). Negative affect was a significant indirect pathway between IWB and WLE (b = 0.01). Conclusions Our results align with previous literature showing that IWB reinforces eating pathology. Interventions targeting negative affect might promote more reasonable WLE. Level of evidence: Level V, cross-sectional descriptive study